El "unravelling" para bigráficas diferenciales - Boza Cordero, Juan (1998)
Here are examined the main properties of the algorithm called ¨unravelling¨ for differential  bigraphs. This algorithm was originally developed for differential graded categories and was useful in the proof the celebrated ¨tame-wild¨ theorem of ¨Drozd´s. First we describe the algorithm, and then we establish in detail the existence of an equivalence between certain subcategories of representations of the original and the derived bigraphs. We also exhibit the precise behaviour of the norm and the quadratic form under the algorithm.